KEPEMIMPINAN DALAM PENDIDIKAN MULTIKULTURAL - Ifnaldi, Ifnaldi; Sartika, Didi; Hadijaya, Yusuf (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
Leadership in multikultural education has become increasingly important as cultural diversity grows around the world. This study aims to explore leadership in multikultural education. This research uses a literature review approach on leadership in multikultural education. The findings of this study indicate that leadership in multikultural education plays a crucial role in creating an inclusive and productive learning environment through a multikultural vision, cultural intelligence, and an inclusive leadership style. By implementing policies that support diversity and collaboration, educational leaders can foster a more tolerant and respectful society.